Quality of life and Associated Factors among Children aged 5 to 18 years with Diabetes Mellitus at St. Francis Hospital Nsambya and Mulago National Referral Hospital - Mulungi-Bibangambah, Esther Nabatanzi; Mworozi, Edison Arwanire; Nyangabyaki, Catherine; Katahoire, Anne R. (International Journal of Diabetes & Metabolic Disorders, 2019)
This study aimed to determine the quality of life and describe associated factors among children aged 5-18 years with diabetes Mellitus at St. Francis Hospital Nsambya and Mulago National Referral Hospital. An explanatory sequential study design was used between November 2018 and March 2019. Univariate analysis together with bivariate logistic regression analysis was used to determine quality of life and identify association between the quality of life at a p-value ? 0.05 respectively. Factors found to have a p-value ? 0.25 were included in the Multivariate logistic regression. A backward method was then applied to determine the best model that predicts quality of life among children. Data was analysed using STATA version 14. Data on the perception of quality of life of children with diabetes mellitus from the perspective of the children, caregivers and health workers was used to obtain qualitative results. 115 children were recruited from the paediatric diabetic clinics. A low quality of life with a mean score of 77 ±15.58 was reported with a mean age of 13 ± 3.9. Factors associated with quality of life included: age groups of 8-12 and 13-18 years, primary education, secondary education, tertiary education, a single parent, living with relatives and primary care giver being a relative other than the biological parents. A sub-optimal quality of life was observed among children with type 1 diabetes mellitus. The factors associated with good quality of life included; age between 5- 7 years, a child living with biological parents, a child being in primary school and higher parental level of education.
Keywords: Quality of life, Type I Diabetes mellitus, Children, Uganda